Genomic evidence for distinct carbon substrate preferences and ecological niches of B athyarchaeota in estuarine sediments - Cassandre Sara Lazar; Brett J. Baker; Kiley Seitz; Andrew S. Hyde; Gregory J. Dick; Kai‐Uwe Hinrichs; Andreas P. Teske (Environmental Microbiology, 2016)
Summary Investigations of the biogeochemical roles of benthic A rchaea in marine sediments are hampered by the scarcity of cultured representatives. In order to determine their metabolic capacity, we reconstructed the genomic content of four widespread uncultured benthic Archaea recovered from estuary sediments at 48% to 95% completeness. Four genomic bins were found to belong to different subgroups of the former Miscellaneous Crenarcheota Group ( MCG ) now called B athyarchaeota: MCG ‐6, MCG ‐1, MCG ‐7/17 and MCG ‐15. Metabolic predictions based on gene content of the different genome bins indicate that subgroup 6 has the ability to hydrolyse extracellular plant‐derived carbohydrates, and that all four subgroups can degrade detrital proteins. Genes encoding enzymes involved in acetate production as well as in the reductive acetyl–C oA pathway were detected in all four genomes inferring that these Archaea are organo‐heterotrophic and autotrophic acetogens. Genes involved in nitrite reduction were detected in all B athyarchaeota subgroups and indicate a potential for dissimilatory nitrite reduction to ammonium. Comparing the genome content of the different B athyarchaeota subgroups indicated preferences for distinct types of carbohydrate substrates and implicitly, for different niches within the sedimentary environment.